PENGARUH SELERA DAN PERSEPSI HARGA TERHADAP PEMBELIAN ULANG PRODUK AYAM GORENG SARI LAUT DI KOTA SUNGGUMINASA-GOWA - Paly, Muhammad Basir (Universitas Galuh, 2023)
Ayam Goreng Sari Laut (AGSL) is very familiar as fast food for urban consumers. This study aims to estimate the effect of taste and perceived price on AGSL repurchase. Using a survey method of 285 consumers as a sample. The variables measured are taste (X1), price perception (X2), and repurchase (Y). Data is collected through online questionnaires which are distributed to consumers. Test the validity and reliability of the data collected. Then proceed with the model feasibility test and determinants, F test and t test. The results of the analysis show that all items and variables used are valid and reliable. The model feasibility test obtained the value of r = which means feasible, the determinant value was obtained 0.57.76%, which means that Y is determined at 57.76% by X1 and X2; the rest is determined by other variances outside the model. The F test shows a very significant effect (sig<0.01), while the t test also proves that X1 and X2 have a very significant effect (sig<0.01) on repeat purchases. This study concludes that AGSL traders need to maintain current consumer tastes and price perceptions.